TOURISM IN THE WORLD AND UZBEKISTAN ECONOMY PLACE AND ROLE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In an era of globalization, tourism is one of the fastest growing industries. According to scientists, in the XXI century, the tourism industry is expected to become the most profitable sector in the world. Today, tourism is the third largest industry after the automotive and oil refining industries. Tourism also has a significant impact on the country's infrastructure. Along with tourism, it will lead to the development of transport, food, hotels, trade, handicrafts, construction and other services in the region. It also serves to modernize the country’s appearance, develop the hotel and restaurant industry, and build links between industries such as transportation and communications systems.